Solving delay differential equations using intervalwise partitioning by Runge–Kutta method - Ismail, Fudziah; Suleiman, Mohammed (Elsevier, 2001)
Embedded singly diagonally implicit Runge-Kutta method is used to solve stiff systems of delay differential equations. The delay argument is approximated using Newton divided difference interpolation. Initially the whole system is considered as nonstiff and solved using simple iteration, in the event that stiffness is indicated, the whole system is considered as stiff and solved using Newton iteration. Numerical results based on one technique to detect stiffness is tabulated and compared with the numerical results when the system is considered as stiff from the beginning. © 2001 Elsevier Science Inc.